On a technique for deriving explicit transfer matrices of orthotropic layers - Vinh, Pham Chi; Linh, Nguyen Thi Khanh; Anh, Vu Thi Ngoc (Vietnam Journal of Mechanics, 2015)
This paper presents  a technique by which the transfer matrix in explicit form of an orthotropic layer can be easily obtained. This transfer matrix is applicable for both the wave propagation problem and the reflection/transmission problem. The obtained transfer matrix is then employed to derive the explicit secular equation of Rayleigh waves propagating in an orthotropic half-space coated by an orthotropic layer of arbitrary thickness.